Inhibition of choroidal osteoma progression using bisphosphonate and RANKL-inhibitory treatment - Mélanie Hébert; Kelly Babic; Edward C. Hsiao; Armin Afshar; Nisha Acharya; John A. Gonzales (American Journal of Ophthalmology Case Reports)
Purpose: To describe the use of anti-osteoclastic medications (i.e., bisphosphonates and receptor activator of nuclear factor kappa beta (RANK) ligand inhibitors) in treating choroidal osteoma. Methods: A 42-year-old male with bilateral posterior choroidal osteomas showed extensive outer retinal atrophy in the right eye secondary to decalcification of a choroidal osteoma and progressive extension of retinal pigment epithelial atrophy in the left eye encroaching on the macula with subtle changes in the choroidal osteoma. Bisphosphonates (i.e., oral alendronate 70 mg weekly) or RANK ligand inhibitors (i.e., subcutaneous denosumab 60 mg every six months) were initiated to prevent calcium resorption. Results: After the introduction of more directed therapy, there was stabilization of the patient's condition over the next nine years while under bisphosphonate treatment, followed by a switch to RANK ligand inhibitor therapy and later bisphosphonate treatment again. This was made evident through stability in fundus photography, enhanced depth imaging optical coherence tomography, and B-scan ultrasonography regarding outer retinal layers thickness, and choroidal osteoma thickness and calcification. Conclusion: Anti-osteoclastic therapy using bisphosphonates or RANK ligand inhibitors could be a new treatment paradigm to prevent resorption of choroidal osteomas and prevent the subsequent atrophy of outer retinal layers. Summary statement: A patient with bilateral posterior choroidal osteomas was treated with bisphosphonates and RANK ligand inhibitors to prevent osteoma resorption in the better-seeing left eye. This has led to stability over six years of outer retinal layers thickness, choroidal osteoma thickness, and choroidal osteoma calcification.